Humane Development : Participation and Change Among the Sadama of Ethiopia. - Hamer, John (University of Alabama Press, 1987)
""Hamer has produced a very well-written ethnographic analysis of development and change among the Sadama, a Cushitic-speaking people living along the Rift Valley ... The analysis attempts to show how traditional modes of decision making and living adapt to or are adapted to impinging forces of modernization. Hamer's emphasis on humane development is highly appropriate and his analysis is very successful. The focus on inevitable and constant change, and the continuing evolution of the society, makes this study a particularly useful one because the lessons of the Sadama can be generali.